Morality Effects and Consumer Responses to Counterfeit and Pirated Products: A Meta-analysis - Eisend, Martin (Journal of business ethics, 2019)
Acquisition and purchase of counterfeit and pirated products are illicit and morally questionable consumer behaviors. Nonetheless, some consumers engage in such illicit behavior and seem to overcome the moral dilemma by justification strategies. The findings on morality effects on consumer responses to counterfeit and pirated products are diverse, and the underlying theories provide no clear picture of the process that explains how morality and justification lead to particular consumer responses or why consumers differ in their responses. This study presents a meta-analysis of 788 effect sizes from 207 independent samples provided in 196 manuscripts that synthesizes the research on the influence of morality on attitudes, intentions, and behavior toward counterfeit and pirated products. The meta-analysis tests competing theoretical models that describe the morality-justification processes, and identifies the deontological–teleological model as the superior one. The meta-analysis further shows that the institutional and social context of consumers explains the differences in morality effects on justifications and responses to counterfeit and pirated products, and provides evidence for the context-sensitivity of the underlying theories.